2016
DOI: 10.1111/nph.13928
|View full text |Cite
|
Sign up to set email alerts
|

The role of phosphorus, magnesium and potassium availability in soil fungal exploration of mineral nutrient sources in Norway spruce forests

Abstract: SummaryWe investigated fungal growth and community composition in buried meshbags, amended with apatite, biotite or hornblende, in Norway spruce (Picea abies) forests of varying nutrient status. Norway spruce needles and soil collected from forests overlying serpentinite had low levels of potassium and phosphorus, those from granite had low levels of magnesium, whereas those from amphibolite had comparably high levels of these nutrients.We assayed the fungal colonization of meshbags by measuring ergosterol con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 80 publications
(82 reference statements)
7
42
2
1
Order By: Relevance
“…However, observations of S. bovinus did not support our hypothesis of enhanced biofilm formation and/or fungal hyphal attachment to surfaces ( Figures 5C and 6C). All these fungal species are described as able to weather silicates in soil environments in association with a host [20,24,41,[51][52][53][54], which is supported by the bulk composition data, but surface attachment of fungal hyphae and biofilm/EPS coverage proved to be minor contributors to the potassium and calcium release under our experimental conditions.…”
Section: Rhizospheric Mineral Alterations and Biofilm Formationsupporting
confidence: 64%
See 1 more Smart Citation
“…However, observations of S. bovinus did not support our hypothesis of enhanced biofilm formation and/or fungal hyphal attachment to surfaces ( Figures 5C and 6C). All these fungal species are described as able to weather silicates in soil environments in association with a host [20,24,41,[51][52][53][54], which is supported by the bulk composition data, but surface attachment of fungal hyphae and biofilm/EPS coverage proved to be minor contributors to the potassium and calcium release under our experimental conditions.…”
Section: Rhizospheric Mineral Alterations and Biofilm Formationsupporting
confidence: 64%
“…After germination, 45 of the most vigorous seedlings of Scots pine were inoculated with one of the pure cultures of the three ectomycorrhizal fungi (15 each) obtained from the Swedish University of Agricultural Sciences, Uppsala, Sweden: Paxillus involutus (PI), Suillus bovinus (SB), and Piloderma fallax (PF). These fungi were selected because they are commonly found in natural Scots pine forests and they have been grown successfully under laboratory conditions [20,24,41,[51][52][53][54]. Scots pine inoculation was carried out at Lund University, Sweden, on a peat-vermiculite and MMN (Marx-Melin-Norkrans) sterilized medium in a volume ratio of 1:5:3 [55] (Table S1) in round, sealed Petri dishes with the seedlings protruding through a notch cut into the Petri dish.…”
Section: Seed Germination and Inoculationmentioning
confidence: 99%
“…Soil Mn levels are known to influence ECM fungi differentially [75]. Calcium and Mg are important plant macronutrients but have not been found to influence ECM community composition or favor certain ECM species in other studies [76]. The specific mechanism(s) driving this response is beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 83%
“…In coniferous trees, elevated CO 2 has been shown to increase the ratio of root to shoot biomass (Alberton et al 2007;Janssens et al 2005) and allocation to mycorrhizal symbionts (Fransson et al 2010;Compant et al 2010) 10 indicating an increased exploration of the soil environment to obtain nutrients. Studies in Swedish (Almeida et al 2018) and Czech (Rosenstock et al, 2016) Norway spruce forests have observed increased belowground allocation to fine roots and ectomycorrhizal hyphal growth and greater preference for growth around apatite (a mineral source of Ca and P) mineral grains under phosphorus-limiting conditions.…”
Section: Introductionmentioning
confidence: 99%